Towards solar cell emitters based on colloidal Si nanocrystals. Issue 1 (14th August 2014) - Leendertz, Caspar; Chirvony, Vladimir S.; García‐Calzada, Raúl; Görög, Lukáš; Töfflinger, Jan Amaru; Korte, Lars; Agouram, Saïd; Martínez‐Pastor, Juan; Petermann, Nils; Wiggers, Hartmut; Ulyashin, Alexander G.
<x xml:space="preserve">Abstract</x> The application of layers of doped colloidal silicon nanocrystals sandwiched between hydrogenated amorphous silicon layers as emitters in silicon heterojunction solar cells is explored. It is shown that such emitters provide excellent interface passivation and reasonable conductivity. Final solar cells with such nanoparticle emitters reach conversion efficiencies on the same level as solar cells with conventional hetero emitters. Quantum efficiency measurements indicate that the light absorbed in the nanocrystals contributes to the current extracted from the solar cell. The remaining challenges that need to be addressed before the application of such colloidal silicon nanocrystals for the processing of low‐cost and potentially printable emitter layers becomes feasible are discussed.